Population-based study of human papillomavirus infection and cervical neoplasia in Athens, Greece - Kroupis, C.; Thomopoulou,G.; Papathomas,T.G.; Vourlidis,N.; Lazaris, AC (Epidemiol.Infect., 2007)
The aim of our study is to describe the prevalence of the different HPV types in women with pre-neoplastic lesions of the cervix in Greece. Cervical scrapes from 841 women were obtained for both cytological evaluation and analysis for the presence of HPV DNA. PCR was performed on specimens from these 841 women. The Pap test results were normal or showed benign cellular changes in 45.8% of the women, atypical squamous cells of undetermined significance (ASCUS) in 23.2%, low-grade squamous intra-epithelial lesion (LSIL) in 27.9% and high-grade squamous intra-epithelial lesion (HSIL) in 3.1%. HPV DNA was demonstrated in 23.6% of cytologically normal women. We detected HPV in 60% of the total samples. Of these, HPV-16 was the most common HPV DNA detected. Interestingly, HPV-58 was inversely correlated with positive cytological findings. A clear pattern of decreasing prevalence of HPV with age was also observed. Our results indicate that HPV infections, especially those with HPV-16, represent a significant public health concern in Greece
DA - 20070806 IS - 0950-2688 (Print) IS - 0950-2688 (Linking) LA - eng PT - Journal Article SB - IM
Keywords: Adolescent; Adult; Aged; analysis; classification; Complications; Epidemiology; Female; genetics; Greece; Humans; isolation & purification; Middle Aged; Papillomaviridae; Papillomavirus Infections; pathology; Population Surveillance; Precancerous Conditions; Uterine Cervical Neoplasms; Vaginal Smears; virology